Utilization of wastewater treatment sludge in the production of fired clay bricks: An approach towards sustainable development - Detho, Amir; Abdul Kadir, Aeslina; Ahmad, Suhaili (Elsevier, 2024)
Wastewater treatment sludge has increase due to the increasing of population and economic potential. Sludge generally contains heavy metals that could lead to environmental effect as well as to human health. This study is focus on utilization of sludges into incorporated fired clay brick. The samples of sludge were gathered from IWK in Perwira and Senggarang. The heavy metal concentration in the wastewater treatment sludge was identified using X-Ray Fluorescence. Sludges were incorporated into bricks at various percentages: 0 %, 1 %, 5 %, 10 %, 20 %, and 30 %. The physical and mechanical characteristics of brick after being integrated with both types of sludges were identified. Furthermore, heavy metals leachability of sludge bricks was tested. The findings reveal that Barium (Ba) has the highest heavy metal concentration in the raw materials, and the chemical composition is Silicon Dioxide (SiO2). Bricks with 5 % sludge content exhibited optimal physical and mechanical attributes for both sludge types. However, sludge from Senggarang exhibited the better results compared to Perwira sludge. In terms of leachability, heavy metals were analysed in bricks from both sludge types. Bricks containing up to 20 % sludge from Senggarang exhibited the lowest heavy metal leachability. Nevertheless, value of heavy metals from both sludges is complied with USEPA standard. In conclusion, 5 % of both sludges is the best percentage to be utilized into fired clay brick by considering it properties and leachability. This study also demonstrated that adopting cleaner production techniques for building bricks can make a substantial contribution towards attaining Sustainable Development Goals (SDGs).